The Misrepresentation of Atheists in Online Media: A Critical Discourse Analysis Perspective - Yusup Supyani (Poltanesa, 2025)
The aim of this research is to unravel ideology in Religion News Text about Atheists in Online News, namely Deutsche Welle (DW), The Times of India and ABS CBN Corporation by applying Critical Discourse Analysis (CDA) approaches. The method applied in this research is descriptive qualitative research. The data of this research are words, phrases and sentences to unravel ideological representation based on Roger Fowler and Ruth Wodak and Michael Meyer’s Critical Discourse Analysis frameworks in religion news text about atheists and nonbelievers. Data collection techniques conducted in this research are data reduction, data presentation, verification and concluding the research based on the frameworks. The findings of the study related to modality and vocabulary classification indicated that ideological representations occurred in news article about atheists and nonbelievers were used to discriminate the presence of atheists and nonbelievers or even a minority one. In addition, ideological representations related to the aspects of grammar eliminated the subjects or the doers in passive voice. As for nominalization, it had the potential to blur the subject by shifting focus from the action to simply presenting an event. Consequently, the ideological portrayal in the news might contribute to the marginalization of specific atheists and nonbelievers featured in the stories, concentrating the reader’s attention exclusively on the event, which could lead to the outcomes typically linked with nominalized sentences on three media online, namely Deutsche Welle, The Times of India and ABS-CBN Corporation. Furthermore, in Indonesia, atheists and nonbelievers are often perceived negatively as they are seen as an “other” group.